2015
DOI: 10.1111/opec.12049
|View full text |Cite
|
Sign up to set email alerts
|

Oil price uncertainty and savings in South Africa

Abstract: Oil prices have become increasingly important to determine indicators such as inflation; this in turn affects savings and investments. This paper investigates the impact of the volatility of oil prices on savings in South Africa using quarterly data covering the period 1960 to 2014.The study used the GARCH-in-mean VAR model. This model also provides a way of examining the effect of a negative and positive shock in oil prices on savings. The outcome of this study proves that oil price uncertainty which is measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Wen et al ( 2022 ) found that a rise in monetary policy uncertainty affects stock returns in South Africa using a quantile-on-quantile paradigm. Dave and Aye ( 2015 ) investigated the impact of oil price uncertainty on savings in South Africa and discovered that uncertainty reduces savings. Similarly, Salisu and Isah ( 2021 ), who looked into the moderating role of EPU in the capital flight-growth nexus from 1986 to 2010, revealed that uncertainty in macroeconomic policies exacerbates capital flight's negative impact on economic growth in South Africa and the rest of Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Wen et al ( 2022 ) found that a rise in monetary policy uncertainty affects stock returns in South Africa using a quantile-on-quantile paradigm. Dave and Aye ( 2015 ) investigated the impact of oil price uncertainty on savings in South Africa and discovered that uncertainty reduces savings. Similarly, Salisu and Isah ( 2021 ), who looked into the moderating role of EPU in the capital flight-growth nexus from 1986 to 2010, revealed that uncertainty in macroeconomic policies exacerbates capital flight's negative impact on economic growth in South Africa and the rest of Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%